2016
DOI: 10.1515/bioeth-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of degraded husked sorghum grains to ethanol

Abstract: Efficient starch saccharification is an essential step towards achieving improved ethanol yields by fermentation. Sorghum grains are important starch sources for bioconversion to ethanol. In the present study, disease degraded (spoilt) husked grains from Nigerian sorghum cultivars were obtained from field sites and subjected to bioprocessing to ethanol. The crude husked grains (comprising husks, spikelet, awn, rachis and pubescence materials) were hammer milled and each meal separately mashed with enzyme cockt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Simple sugars, which can be immediately turned into ethanol, need to be pretreated [8]. A mixture of fermentable sugars and possible inhibitory substances found in the biomass structure are released during pretreatment and hydrolysis [9,10]. The most efficient way to release simple sugars from cellulosic materials is through hydrolysis employing the right enzymes, however, process rates must be improved and enzyme production costs must be reduced [11].…”
Section: Introductionmentioning
confidence: 99%
“…Simple sugars, which can be immediately turned into ethanol, need to be pretreated [8]. A mixture of fermentable sugars and possible inhibitory substances found in the biomass structure are released during pretreatment and hydrolysis [9,10]. The most efficient way to release simple sugars from cellulosic materials is through hydrolysis employing the right enzymes, however, process rates must be improved and enzyme production costs must be reduced [11].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the literature contains only recommendations for the use of Hitempase 2XL in the production of ethyl alcohol. Nasidi et al [7] showed that the mixture of EP (Promalt, Bioglucanase ME1250L, Hitempase 2XL, Promalt 4TR and Termamyl 120L) allows to convert the spoiled grains of sorghum into bioethanol. The main attention was paid to the influence of the type of raw material on the technological parameters of the process.…”
Section: Introductionmentioning
confidence: 99%